PENGARUH NEGATIVE FRAMING DAN ADVERSE SELECTION TERHADAP PENGAMBILAN KEPUTUSAN ESKALASI KOMITMEN: (Studi Empiris pada Mahasiswa Akuntansi Universitas Malikussaleh) - Yusra, Muhammad; Atika, Surya (Department of Accounting, Faculty of Economics & Business, 2017)
This study aims to determine the effect of negative framing and adverse selection on commitment escalation decision making. The data used in this study are primary data. The population in this study are 178 active students majoring in Accounting of economics and business faculty, Malikussaleh University in 2014. The number of samples that met the research criteria were 64 students taken using a random sampling. The method used to analyze the relationship between the independent variable and the dependent variable is the technique of analyzing two ways ANNOVA using factorial 2 x 2 designs with instruments in the form of cases.The test results show that negative framing effect on commitment escalation, adverse selction effect on commitment escalation, and negative framing and adverse selection have no effect on commitment escalation.